Acessibilidade arquitetônica do consultório de enfermagem da unidade básica de saúde - Pessoa, Ana Talyne (2018)
Health establishments must have architectural accessibility in order to offer all people, including those with disabilities, access to their services. It is necessary, therefore, that the units be constructed considering the parameters of accessibility established in the Norma Brasileira Regulamentadora 9050 of the Brazilian Association of Technical Norms. The nurse as educator and, often, manager of these units, must also know the existence of the Standard. Thus, they will be able to participate in the elaboration and execution of projects in renovations and constructions of health units. Because it is an extensive and difficult to understand standard, professionals can make use of educational technologies to their knowledge. This study aimed to validate an educational primer on architectural accessibility of the nursing office of the Basic Health Unit; develop and evaluate content with experts; construct educational booklets; evaluate content and appearance of educational primer with experts. This is a methodological research. The following steps were followed: selection of material for content construction; construction of textual script and its validation with specialists in accessibility; construction of educational booklet with graphic designer; and validation of appearance with specialists in Primary Health Care. Two instruments were used to collect data, the first, Instrument of Validation of Educational Content in Health, for validation of the textual script and the second, Suitability Assessment of Materials, for validation of the appearance of the educational booklet. In relation to the data analysis, we used the Concordance Percentage and the Cronbach's alpha. Regarding the evaluation of the textual script, it was considered valid by all experts after three meetings. As for the evaluation of the educational booklet, this was considered valid in content and appearance by all experts.